Semiochemicals in integrated pest management: Molecular chemistry, biosynthesis mechanisms, and application in sustainable agricultural systems - Choudhary, Arbind Kumar; R, Abirami (Journal of Biopesticides and Agriculture Technology, 2026)
Background: Semiochemicals, including volatile and non-volatile organic compounds used in insect communication, offer environmentally friendly alternatives to broad-spectrum pesticides. In particular, sex pheromones have gained prominence in Integrated Pest Management (IPM) due to their species-specific action and reduced ecological impact. Understanding their chemical structures, biosynthetic pathways, and olfactory mechanisms is essential to optimize their application across diverse crop systems. Methods: This study presents a comprehensive review of 15 peer-reviewed publications (2010–2025). It synthesizes findings on pheromone chemistry, enzymatic biosynthesis pathways, olfactory reception mechanisms, and field-level applications. The analysis integrates molecular characterization, biochemical pathways, and empirical performance data from 35 major agricultural pests to evaluate efficacy and economic impact. Findings: Lepidopteran sex pheromones primarily consist of Type I (C₁₀–C₁₈ unsaturated alcohols, aldehydes, acetate esters; ~75%) and Type II (C₁₇–C₂₃ polyunsaturated hydrocarbons; ~15%) compounds. Biosynthesis involves key enzymes such as ACC, FAS, Δ12-desaturase, and FAR. Olfactory detection occurs via GPCR-mediated signal transduction in antennal sensilla. Field evidence shows pheromone-based strategies—monitoring, mass trapping, mating disruption, and attract-and-kill—achieve 60–95% pest suppression while reducing pesticide costs by an average of 59%. Controlled-release formulations enable sustained delivery for 30–120 days. Conclusion: Semiochemical-based IPM represents a scientifically validated, cost-effective, and environmentally sustainable pest control strategy. By targeting species-specific communication systems, it reduces chemical dependency while maintaining high suppression efficiency. Novelty/Originality of this Article: This review integrates molecular chemistry, enzymatic biosynthesis, neuro-olfactory mechanisms, and large-scale field validation into a unified analytical framework. By linking mechanistic biochemical insights with applied agricultural performance data, it strengthens the scientific foundation and practical justification for semiochemical-driven IPM as a sustainable alternative to conventional pesticide regimes.